Determination of the strain-rate sensitivity of ultrafine-grained materials by spherical nanoindentation. Issue 8 (6th March 2017) - Feldner, Patrick; Merle, Benoit; Göken, Mathias
Abstract: Abstract : The strain-rate sensitivity of the flow stress represents a crucial parameter for characterizing the deformation kinetics of a material. In this work a new method was developed and validated for determining the local strain-rate sensitivity of the flow stress at different plastic strains. The approach is based on spherical nanoindentation strain-rate jump tests during one deformation experiment. In the case of ultrafine-grained Al and ultrafine-grained Cu good agreement between this technique and macroscopic compression tests has been achieved. In contrast to this, individual spherical nanoindentation experiments at constant strain-rates resulted in unrealistically high strain-rate sensitivities for both materials because of drift influences. Microstructural investigations of the residual spherical imprints on ultrafine-grained Al and ultrafine-grained Cu revealed significant differences regarding the deformation structure. For ultrafine-grained Cu considerably less activity of grain boundary sliding has been observed compared to ultrafine-grained Al.